The prognostic value of absolute lymphocyte count and neutrophil‐to‐lymphocyte ratio for patients with metastatic breast cancer: a systematic review and meta‐analysis - Sang, Bulin; Fan, Yuxin; Wang, Xurao; Dong, Lixian; Gong, Yuanyuan; Zou, Wenhong; Zhao, Guanhua; He, Jianchang (Frontiers in Oncology, 2024)
Background: Neutrophil-to-lymphocyte ratio (NLR) is considered a potential prognostic marker in early breast cancer. However, the prognosis of absolute lymphocyte count (ALC) and NLR in metastatic breast cancer (MBC) is reported in a few studies and conclusions are still conflicting. This present manuscript was aim to provide further solid evidence regarding the prognostic values of ALC and NLR in MBC patients.Method: Eligible studies that reported the associations between ALC or NLR and MBC were included by searching relative electronic databases. Overall survival (OS) and progression-free survival (PFS) were used as outcome measures. The hazard ratio (HR) values and 95% confidence interval (CI) of the outcome measures were collected as effect sizes, and further analysis and discussion were conducted according to the pooled HR, subgroup analysis, publication bias and inter-study heterogeneity.: Twenty-nine studies comprising 3973 patients with MBC were included. According to our findings, lower ALC was significantly associated with poorer prognosis of OS [HR=0.57, (95% CI 0.48 to 0.68)] and PFS [HR=0.68, (95% CI 0.58 to 0.79)], and the greater NLR was associated with poorer OS [HR=1.50, (95% CI 1.35 to 1.67)] and PFS [HR=1.82, (95% CI 1.42 to 2.35)]. Furthermore, the prognostic values of ALC and NLR in MBC were also observed in the subgroup analyses regarding cut-off values and ethnicities. Conclusion: Low ALC and elevated NLR were observe to be significantly associated with adverse OS and PFS in MBC, indicating that ALC and NLR may act as potential prognostic biomarkers of MBC patients. Meanwhile, our results will also provide some novel evidences and research clues for the selection and development of clinical treatment strategies in MBC patients.